Analisis faktor-faktor yang mempengaruhi pendapatan pedagang kaki lima di Kota Jambi (studi kasus warung manisan Kecamatan Telanaipura) - Ravisca Aulia Inderianti; Hardiani Hardiani; Rosmeli Rosmeli (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to: 1) To determine and analyze the socio-economic characteristics of street vendors at candied stalls in Telanaipura District, Jambi City. 2) knowing and analyzing the factors that influence the income of street vendors at candied stalls in Telanaipura District, Jambi City. The research analysis tool uses multiple linear regression analysis tools. Based on the results of multiple linear regression, it can be concluded that simultaneously the independent variable fixed capital, operating capital, working hours, length of business, and location have a significant effect on the dependent variable income of the candied warung merchants and partially only the operating capital and working hours variables have a significant effect on traders' income. candied stalls, while the variables of fixed capital, length of business, and location did not have a significant effect on the income of the candied stall traders. Furthermore, the R-square value is 0.923. This means that 92.3 percent of the variation in the income of the candied shop traders is explained by the variables in this study, while the remaining 7.7 percent is explained by other variables outside the research. Keywords: Income, Fixed capital, Operating capital, Working hours, Length of business, location